Incidence of Dental Caries and Associated Factors in the School Period in a Municipality in Southern Brazil - Andréia Clara Nazário; Jefferson Traebert; Eliane Traebert (Association of Support to Oral Health Research (APESB), 2023)
Objective: To estimate the incidence of dental caries and associated factors in the school period from six/seven to ten years of age. Material and Methods: A longitudinal study involving 168 children was followed up between 2015 and 2019 in the municipality of Palhoça, Brazil. The dependent variable was the caries incidence rate in the mixed dentition. The independent variables included information regarding demographic and socioeconomic status. Multivariate analyzes were carried out using Poisson Regression with a robust estimator. Variables with p <0.20 in the bivariate analysis were included in the adjusted model. Relative risks were estimated, as well as 95% confidence intervals. Results: Of 168 followed schoolchildren, 32 developed the disease, providing an incidence rate of 19.0%. Female children had a 10% higher risk [RR = 1.10 (95% CI 1.03; 1.18)] of developing caries than males. Also, children born from fathers with ≤ 8 years of schooling at baseline had a 9% higher risk [RR = 1.09 (95% CI 1.01; 1.16)] of developing dental caries compared to fathers with higher education. Conclusion: The incidence of dental caries in a four-year period was 19.0%. Females and children born from fathers with a lower level of education showed higher incidence rates.